The Indian Anomaly: Rethinking Credit Rating Agency Regulation from the Economic Perspective of Hyman Minsky - Kirshner, Jodie A. (Columbia Journal of Asian Law, 2013)
Policymakers have blamed credit rating agencies for the recent financial crisis – but they could be wrong. India can aid in understanding whether the agencies can still be relied upon as private “gatekeepers” in financial markets, or whether public institutions must take primary responsibility. The economist, Hyman Minsky, advocated for robust public regulation and a limited role for private actors. India can be seen as an example of his theories. If India’s agencies cannot prevent speculative credit from causing future economic problems, the problems could suggest that more structural measures are necessary to counter instability, as Minsky predicted. Analyzing India and the credit rating agencies through the frame of Minsky’s economic theories offers insights into how best to reform financial regulation to prevent future economic collapse.